Recent Advances in the Evaluation and Treatment of Primary Angle Closure Disease (Canadian Eye Care Today, 2024)
In the realm of ophthalmology, the clinical management of angle closure remains a disputed topic. An aging population, underperformance of gonioscopy, and a paucity of clear guidelines about management have contributed to the rising number of patients with primary angle closure glaucoma (PACG). The global prevalence of PACG based on a meta-analysis published in 2014 was 0.50%, with the highest prevalence occurring in Asian populations. This study also projected that the number of people with PACG worldwide will increase to 32 million by the year 2040. PACG is a visually devastating disease; around a quarter of individuals worldwide and one out of nine individuals in the United States with newly diagnosed PACG are affected by blindness (visual acuity of 20/200 or less). The rising burden of the visual morbidity associated with untreated PACG highlights the urgent need for more clearly defined, evidence-based practice guidelines in angle closure care.